Trauma and Madness in Mental Health Services - Hunter, Noël (Springer International Publishing, 2018)
How do survivors of child abuse, bullying, chronic oppression and discrimination, and other developmental traumas adapt to such unimaginable situations? It is taken for granted that experiences such as hearing voices, altered states of consciousness, dissociative states, lack of trust, and intense emotions are inherently problematic. But what does the evidence actually show? And how much do we still need to learn?